2004
DOI: 10.1002/dir.20018
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pre- and post-purchase service on prices in the online book market

Abstract: We examine the ability of customer ratings of pre-purchase and post-purchase service to explain price variations in the online book market. In addition, we test whether market leaders leverage their branding advantage by charging higher prices. E-tailer prices were modeled using a market basket of identical books whose posted prices were sampled repeatedly over a 4-month period. Contrary to expectations, posted prices were relatively constant across the time period that included a highly competitive 2000 holid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 15 publications
1
31
0
1
Order By: Relevance
“…As the primary aim of relationship marketing is to increase the frequency and volume of consumption, it follows that variance in the quality of the relationship-marketing effort may be related to an observable difference in the financial risk perceptions. This assumption is consistent with the findings of Cao and Gruca (2004), who found that as postpurchase satisfaction, and accordingly future purchase intentions, increased for the three largest online book retailers, so too did the customer's tolerance for financial risk. Furthermore, as it is foreseeable that different online retailers will exhibit different levels of relationship-marketing competency, we hypothesize the following: H2: (a) Perceptions of relationship-marketing quality (RMQ) will vary with different levels of financial risk, and (b) this variation will be affected by different retailers.…”
Section: Impact On Relationship-marketing Qualitysupporting
confidence: 90%
See 2 more Smart Citations
“…As the primary aim of relationship marketing is to increase the frequency and volume of consumption, it follows that variance in the quality of the relationship-marketing effort may be related to an observable difference in the financial risk perceptions. This assumption is consistent with the findings of Cao and Gruca (2004), who found that as postpurchase satisfaction, and accordingly future purchase intentions, increased for the three largest online book retailers, so too did the customer's tolerance for financial risk. Furthermore, as it is foreseeable that different online retailers will exhibit different levels of relationship-marketing competency, we hypothesize the following: H2: (a) Perceptions of relationship-marketing quality (RMQ) will vary with different levels of financial risk, and (b) this variation will be affected by different retailers.…”
Section: Impact On Relationship-marketing Qualitysupporting
confidence: 90%
“…Prior research has largely failed to examine the impact of retailer differences, and in particular, whether these differences account for variances in the impact of perceived risk on consumer behavior in the online marketplace. It is perhaps noteworthy that the only identified study that has examined the impact of firm differences on financial risk (price sensitivity) in online retail (Cao & Gruca 2004) found that firm-level heterogeneity accounted for 93% of the variance in their model. By controlling for retailer differences when measuring the impact of financial risk on service quality (SQ) and relationship-marketing quality (RMQ) in the online retail context, this study will add to the growing chorus calling for greater consideration of between-subject effects.…”
Section: Financial Risk In Online Shoppingmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of service quality differentiation has been cited as a source of price dispersion in electronic markets because different levels of service are typically associated with different levels of prices (Betancourt and Gautschi 1993, Baylis and Perloff 2002, Pan et al 2002, Cao et al 2003, Cao and Gruca 2004. Betancourt and Gautschi (1993) find that service quality significantly affects price dispersion in traditional markets, such that firms with higher service quality charge higher prices.…”
Section: Hypothesis 1 (H1) Products With Higher Cost Are Associated mentioning
confidence: 99%
“…Although an online store may offer high-quality products at lower prices, the consumer may be skeptical over quality, compared with higher priced but better known online brands. While having a wellknown brand reduces the risks for consumers in doing business with a leading online vendor [7], familiar brands with established records of performance help in building trust [15]. Due to their well-known brands, Internet market leaders are more highly trusted by consumers [62].…”
Section: Brandmentioning
confidence: 99%